Arλ3(λ1, λ2, Ω)-Weighted Inequalities with Lipschitz and BMO Norms. (27th June 2010) - Tong, Yuxia; Li, Juan; Gu, Jiantao
Abstract : We first define a new kind ofA r λ 3 ( λ 1, λ 2, Ω ) two-weight, then obtain some two-weight integral inequalities with Lipschitz norm and BMO norm for Green's operator applied to differential forms.